Preeclampsia as a Risk Factor of Postmenopausal Cardiovascular Disease: A Cross-Sectional Study - Pasquale Palmiero; Pierpaolo Caretto; Francesca Amati; Marco Matteo Ciccone; Maria Maiello (Clinics and Practice, 2025)
Introduction: Preeclampsia (PE) is a pregnancy-specific disorder characterized by hypertension and organ dysfunction, affecting 5–8% of pregnancies globally and increasing women’s long-term risk of cardiovascular disease (CVD). This study investigates the association between prior PE and cardiovascular health in postmenopausal women. Methods: A total of 108 postmenopausal women with a history of PE and 100 controls without PE were enrolled. Clinical data, blood pressure readings, and echocardiographic assessments were obtained. Statistical analysis was conducted using SPSS version 20.0. Results: Women with prior PE showed a higher prevalence of eccentric left ventricular hypertrophy (37% vs. 23%, p < 0.02) and diastolic dysfunction (51% vs. 39%, p < 0.003). Maternal history of hypertension was also more common in the PE group (55% vs. 26%, p < 0.003). Obesity was more frequent in the PE group, but did not reach statistical significance (p < 0.09). Conclusions: Prior PE was linked to an increased risk of postmenopausal cardiac abnormalities, including left ventricular hypertrophy and diastolic dysfunction. A maternal history of hypertension was also more common among women with prior PE, suggesting a familial connection; PE should be acknowledged as a significant predictor of long-term cardiovascular risk, requiring lifelong monitoring and preventive measures.